2013
DOI: 10.1007/s10753-013-9703-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Baicalein in LPS-Stimulated RAW264.7 Macrophages via Estrogen Receptor and NF-κB-Dependent Pathways

Abstract: Baicalein has been used for many years as a popular antiviral and antibacterial in China. Recent investigations revealed that baicalein also has anti-inflammatory activities. Our results indicated that baicalein increases ERE-luciferase activity in an estrogen receptor (ER)-dependent manner when either ERα or ERβ were coexpressed in Hela cells. This study examined whether baicalein exerts an anti-inflammatory effect in RAW264.7 cells through an estrogen receptor-dependent pathway and through regulation of NF-ĸ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 29 publications
6
58
0
Order By: Relevance
“…Moreover, TNF-α is one of the most potent innate immune-activating stimuli. TNF-α exerts its toxic effects by potently activating HSC and inducing the expression of inflammatory cytokines such as IL-1β and IL-6 [21,22]. Our study also confirmed P-Smad3 an upregulated expression of IL-1β, IL-6, and TNF-α in LX-2 cells induced by TNF-α.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, TNF-α is one of the most potent innate immune-activating stimuli. TNF-α exerts its toxic effects by potently activating HSC and inducing the expression of inflammatory cytokines such as IL-1β and IL-6 [21,22]. Our study also confirmed P-Smad3 an upregulated expression of IL-1β, IL-6, and TNF-α in LX-2 cells induced by TNF-α.…”
Section: Discussionsupporting
confidence: 82%
“…Baicalein is a flavonoid isolated from Scutellaria baicalensis Georgi (Huangqin)which possesses anti-inflammatory, anti-oxidative and anti-carcinogenic activities [7][8][9][10]. In additon, baicalein has been shown to attenuate MMP-1 expression in human keratinocytes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Baicalein (5,6,7-trihydroxyflavone) is an active ingredient extracted from the traditional Chinese herb Scutellaria baicalensis Georgi, which has been reported to possess anti-inflammatory, anti-oxidant, anti-cancer and anti-type 2 diabetes properties and is widely used to treat various diseases (Lin, Shen, Lin, Yang, & Chen, 2007;Li-Weber, 2009;Fan et al, 2013;Fu et al, 2014). Baicalein has been reported to stimulate osteoblastic MC3T3-E1 cell differentiation, inhibit osteoclast A c c e p t e d M a n u s c r i p t differentiation and induce mature osteoclast apoptosis to promote bone metabolism (Kim, Lee, Kim, Min, & Kim, 2008;.…”
Section: Introductionmentioning
confidence: 99%